2016
DOI: 10.1038/srep36614
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembling nanomedicine of conjugated linoleic acid-paclitaxel conjugate (CLA-PTX) with higher drug loading and carrier-free characteristic

Abstract: The main objective of this study was to demonstrate the proof-of-principle for the hypothesis that conjugated linoleic acid-paclitaxel conjugate (CLA-PTX), a novel fatty acid modified anti-cancer drug conjugate, could self-assemble forming nanoparticles. The results indicated that a novel self-assembling nanomedicine, CLA-PTX@PEG NPs (about 105 nm), with Cremophor EL (CrEL)-free and organic solvent-free characteristics, was prepared by a simple precipitation method. Being the ratio of CLA-PTX:DSPE-PEG was only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 31 publications
(43 reference statements)
1
51
0
Order By: Relevance
“…Under this circumstance, the safety of these SMMDC NPs might be improved because they possess surfactant-free and organic solvent-free characteristics. 12 In the present research, the MTD value of NPPA-PTX@PEG NPs in healthy ICR mice was almost sixfold than that of Taxol, indicating that the safety of NPPA-PTX@ PEG NPs was significantly enhanced compared to Taxol. We previously demonstrated that the XlogP and Hansen solubility parameters are key factors for predicting SMMDCs self-assembling into NPs.…”
supporting
confidence: 44%
See 2 more Smart Citations
“…Under this circumstance, the safety of these SMMDC NPs might be improved because they possess surfactant-free and organic solvent-free characteristics. 12 In the present research, the MTD value of NPPA-PTX@PEG NPs in healthy ICR mice was almost sixfold than that of Taxol, indicating that the safety of NPPA-PTX@ PEG NPs was significantly enhanced compared to Taxol. We previously demonstrated that the XlogP and Hansen solubility parameters are key factors for predicting SMMDCs self-assembling into NPs.…”
supporting
confidence: 44%
“…Interestingly, these can self-assemble into NPs in water, and their antitumor activity has been confirmed in vitro and in vivo; 11 eg, conjugated linoleic acid-paclitaxel conjugate (CLA-PTX) can self-assemble into NPs. 12 These SMMDC NPs, with higher drug loading and an aqueous solvent with organic solventfree characteristics, can be prepared by a simple precipitation method. 11 The theoretical partition coefficient (XlogP) and Hansen solubility parameters of the SMMDCs might be the key factors for forming self-assembled NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many nanosystems that can be used to deliver cancer drugs, including cross-linked self-assembly nanoparticles, polymersomes, liposomes, and others. [42][43][44][45] Nanocarriers using lipids to load drugs form a carrier system with a number of desirable features, including a low toxicity, a biodegradable particulate matrix, nontoxic degradation products, a high capacity to incorporate lipophilic and hydrophilic drugs, a controlled release of the incorporated drug, and easy scale-up at low cost. 46 For this purpose, different types of lipid carriers, including lipid-drug conjugates, SLNs, and NLCs, have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro antitumor activity of PTX/SPIO-SSL-H 7 K(R 2 ) 2 was evaluated in MDA-MB-231 cell line following our previously reported method. 23,24,[28][29][30][31] Briefly, MDA-MB-231 cells (1×10 4 cells/well) were seeded in 96-well plates and incubated for 24 h. Then, the cells were treated with cell culture medium (pH 6.8 or pH 7.4) containing different amounts of PTXloaded liposomes and incubated for 48 h at 37°C. The cell viability was determined by sulforhodamine B assay.…”
Section: Flow Cytometrymentioning
confidence: 99%